Financing Education Hubs: Who Invests? - Knight, Jane (International Higher Education, 2015)
International Education Hubs require major investments to attract and retain local and international higher education institutions, training organizations, students, research and development centres, and knowledge industries. This article examines the role of public and private financing from local and foreign investors in establishing countries such as Qatar, United Arab Emirates and Malaysia as education hubs.